Pengembangan KOMPAS (Komik IPA SMPP) Interaktif sebagai Media Pembelajaran untuk Meningkatkan Hasil Belajar Peserta Didik pada Materi Sistem Pernapasan Manusia - Rokib, Irma Sari; Fajriyani; Imranah (Program Studi Tadris IPA IAIN Parepare, 2025)
This research focuses on the development of KOMPAS (Komik IPA SMP) Interactive as a learning medium to improve students' learning outcomes on human respiratory system materials. In this study, the problem of how to develop KOMPAS (Komik IPA SMP) media, media validity, media practicality, and media effectiveness is discussed. This study aims to determine the development of KOMPAS (Junior High School Science Comics) media, the validity of KOMPAS (Junior High School Science Comics) Interactive, the practicality and effectiveness of KOMPAS (Junior High School Science Comics) Interactive media. This research uses the Research and Development (R&D) method with a 4D research model starting from the definition stage, the design stage, the development stage, and the dissemination stage. The mechanism of data collection is through observation, interviews, questionnaires, tests, and documentation. Data analysis applies data validity tests, data practicality tests, and data effectiveness tests. The results of the study show 1) the development of KOMPAS (Junior High School Science Comics) as a learning medium to improve students' learning outcomes on human respiratory system material through various stages starting from define, design, development, and disseminate; 2) The validation of KOMPAS (Junior High School Science Comics) Interactive is in the very valid category with a percentage of 94% 3) The practicality of KOMPAS (Junior High School Science Comics) is in the very practical category with a percentage of 86%; 4) the effectiveness of KOMPAS (Interactive Junior High School Science Comics) is in the very practical category with a percentage of 86.16%; 4) The effectiveness of KOMPAS (Junior High School Science Comics) Interactive is considered effective to be used as a source of Biology learning because the N-Gain score obtained is 0.72 which if categorized has increased with high effectiveness.